Some attempts to detect genetic differences between populations of small balsam (Impatiens parviflora DC.) - Komosińska, Emanuela; Wódkiewicz, Maciej; Jarzyna, Ingeborga; Jarochowska, Emilia; Milanowski, Rafał; Chwedorzewska, Katarzyna; Wyszomirski, Tomasz (Biodiversity: Research and Conservation, 2006)
Invasive plants populations often originate from a few individuals, thus they may show very low genetic variability. On the other hand, differences between local populations can result from a rapid evolutionary change, which may play important role in the invasion process. We attempt to detect genetic differences between two Polish populations of small balsam, an annual plant highly invasive in Europe. Studies are conducted in parallel at two levels: morphological (by common garden experiments) and molecular (using AFLP method). AFLP shows no differences between the two populations, but the results obtained for some morphological measurements suggest that slight genetic differences between the two populations exist. Possibly they are too small to be detected through AFLP technique. Some of them can result from maternal effects; this is to be checked in further research.